Kalker er ikke bare kalker. Et forsøg på at vurdere oversættelseslån - Jacobsen, Birgitte (Nordiske Studier i Leksikografi, 2005)
For historical reasons most ofthe calques in Grecnlandic come from Danish. Some ofthcm are old and well established, others are still on theirway into the language, and not yet generally acceptcd. Ina pilot study 1 invcstigated thc attitude towards difTcrcnt types of ealqucs. Although oldcr informants generally accept fcwcr ealqucs than youngcr informants, there is grcat individual variation. But also thc form, content and funetion of calques seem to play a role in their spreading and use, and may serve as useful background criteria for selcetion. Introdueing ealqucs in (Greenlandic) dietionaries pose specific problems with respeet to authorization of non-genuine expressions.